Methods of explaining the linguistic material according to Al-Bayhaqi (544 AH) In his book Springs of Language - Al-Tamimi, Khamis (Al-Adab Journal, 2025)
The research dealt with one of the topics related to the methods followed by the owners of dictionaries in explaining linguistic entries, including Al-Bayhaqi in his book (Yanabi’ Al-Lugha), as I listed in it the methods of explaining the linguistic material that appeared in his book and tried to study and direct them, and provide examples for each method, noting that Al-Bayhaqi did not mention these methods explicitly, but rather we learned about them from the context of explaining the linguistic material, and accordingly the research came under the title (Methods of explaining the linguistic material according to Al-Bayhaqi (544 AH) in his book Yanabi’ Al-Lugha).Since Arabic dictionaries differed in their methods of explaining linguistic material, both in the past and in the present, and also differed in the arrangement of their words, their classification, and the method of controlling their entries, Its methods are many and varied, and each dictionary has its own approach that differs from others in choosing a method for explaining the linguistic material in it; Therefore, I was keen to clarify what Al-Bayhaqi uniquely stated and what those who preceded him among the authors of dictionaries followed in explaining the linguistic material and clarifying its meaning. According to a method based on studying and analyzing each of the methods mentioned in his book.